Floristic-structural relationships between Canga ferruginous tree communities and adjacent vegetation types - Souza, Cléber Rodrigo de; Coelho, Polyanne Aparecida; Oliveira, Henrique Faria de; Morel, Jean Daniel; Araújo, Felipe de Carvalho; Costa, Maria Teresa Rodrigues; Santos, Alisson Borges Miranda; Castro, Gislene de Carvalho; Santos, Rubens Manoel dos (Acta Scientiarum. Biological Sciences, 2018)
Our objective was to evaluate the floristic and structural relationships between Canga tree communities and other vegetation types inserted in the physiognomic units set, in order to test the hypothesis that these communities have unique characteristics due to their specific environmental conditions. For this, we compared the structural and floristic attributes of Canga vegetation with adjacent semideciduous seasonal forest, Savanna and ecotone areas, evaluating the similarity in its behavior. Our results demonstrate the existence of distinct relationships among vegetation types in relation to different perspectives, related to macro-scale environmental attributes and to the phytogeographic context. In general, Canga tree vegetation has its structure associated with open vegetation types, such as the Cerrado (Savanna) and its composition associated with forest vegetation types, constituted by a community with specific ecological characteristics. Our results suggest the presence of ferruginous soils as a factor that contributes to environmental and ecological heterogeneity in vegetation matrices.